Análisis de la presencia de trisomía 8 en las diferentes fases de leucemia mieloide crónica - Beatriz González-Yebra; Francisco Arath Ruiz-Velázquez; Anaid Herrerías-García; Ana Lilia González; Elia Lara-Lona; Daniela Muñoz-López; Lauro Fabian Amador-Medina (Instituto Nacional de Salud Pública, 2023)
No disponible